Penelitian Pendahuluan tentang Pengukuran Performance dan Load Testing pada Learning Management System (LMS) - Qomariyah, Nurul; Subyantoro, Eko; Asrowardi, Imam (Program Studi Teknologi Rekayasa Internet, Politeknik Negeri Lampung, 2023)
This preliminary study aims to measure the performance of the Moodle-based online learning system for Learning Management System (LMS) of Lampung State Polytechnic. This is done by conducting performance and load testing on LMS to gain a deeper understanding of the server performance in handling high user loads. The measurements were carried out using Apache JMeter with predefined scenarios provided by Moodle. The test results showed that most of the services were accessible well and fast, but there were some services that experience increased response time as the number of users increases.